Efficient power inverters for marine energy systems - Ye, Jian. (2014)
Nowadays, multilevel inverters are extensively used in high-power applications, such as laminators, conveyors, pumps, fans, blowers, compressors, and so on. In recent years, a new topology of multilevel inverters called laddered inverters has been proposed. Laddered inverters have the advantages of other topologies of multilevel inverters, like low total harmonic distortion value and high efficiency. Furthermore, laddered inverters have simple structure and straightforward operation. However, this new topology of multilevel inverters has not been fully developed. This thesis focuses on the design of efficient power inverters basing on laddered inverters. The best switching angles have been calculated. The circuit diagrams of trinary laddered inverters have been designed. The simulations of trinary laddered inverters have been made. The simulation results have showed that the calculation results of best switching angles and the design of trinary laddered inverters are valid. The marine energy systems have been modeled based on the designed trinary laddered inverters.